Fungsi Model Kepemimpinan Dalam Mengatur Manajemen Konflik Pada Organisasi : Study di Kantor Bina Marga Malang - Ninda Rachmawati,; Chavid Moyo Jaladri,; Muhammad Habib , (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2022)
This research was aimed at identifying the effects of the function of the leadership model in managing conflict management in organizations. In essence, conflict is a lose-lose battle between groups or individuals who have different interests in the organization, or with one or more parties. If conflicts occur frequently and the resolution is delayed, it will weaken the position of the conflicting parties and the organization as a whole. Therefore, resolving conflicts quickly is very necessary so that the organization does not stagnate. The solution to the conflict that arises depends on the leadership style itself—how the leader manages and resolves conflict both with his subordinates and with other work groups. Using the right leadership style will speed up the resolution of conflicts that occur in the organization without harming one of the parties. Based on the above, the author wants to know if there is a relationship between leadership style and conflict resolution in groups or conflicts between groups in the organization. This research uses a descriptive qualitative research model, which is where the results of this research are. The success of a leader is not only measured by his success in mobilizing individuals to do something, but also by his ability to mobilize his group as a whole. Therefore, leaders need to pay attention to group dynamics, which have their own emotions, affections, sentiments, souls, and personalities. A leader's lack of attention to group dynamics will trigger conflict in the organization or group. In the past, leaders considered the emergence of conflict to indicate that a leader could not or did not succeed in communicating with his subordinates. However, now the conflict is considered a means to increase the productivity and creativity of employees so that it will facilitate the achievement of organizational goals or bring about renewal and change in the organization.